Development and Comparison between Charge Pump Circuit and LTC 3108 Circuit for Thermal Energy Harvester - Yun, Goh Siew; Leong, Kok Swee (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Power conditioning circuit is a very important role for any energy harvester. Therefore, choosing a suitable power conditioning circuit is an important process also. In this paper, two power conditioning circuits which are Charge pump circuit and LTC 3108 circuit are designed and compared. At the same time, the TEG is used as input energy for the circuits. From the input of TEG which is 1.18V, Charge pump need 6 minutes to boost the circuit to 4.06V. However, the LTC 3108 circuit only need 10 seconds to boost up the voltage to 4.92V. Then, decade resistance box is connected to the circuits. Regarding the power output, the power output of both circuits is about the same. However, the matching load of the LTC 3108 circuit is 20kΩ but the matching load for the Charge pump is 50Ω only.